Modulation of Cell Surface Receptor Expression by Modified Vaccinia Virus Ankara in Leukocytes of Healthy and HIV-Infected Individuals - Leite Pereira, Adrien; Jouhault, Quentin; Marcos Lopez, Ernesto; Cosma, Antonio; Lambotte, Olivier; Le Grand, Roger; Lehmann, Michael H.; Tchitchek, Nicolas (Frontiers in Immunology, 2020)
Viral vectors are increasingly used as delivery means to induce a specific immunity in humans and animals. However, they also impact the immune system, and it depends on the given context whether this is beneficial or not. The attenuated vaccinia virus strain modified vaccinia virus Ankara (MVA) has been used as a viral vector in clinical studies intended to treat and prevent cancer and infectious diseases. The adjuvant property of MVA is thought to be due to its capability to stimulate innate immunity. Here, we confirmed that MVA induces interleukin-8 (IL-8), and this chemokine was upregulated significantly more in monocytes and HLA-DRbright dendritic cells (DCs) of HIV-infected patients on combined antiretroviral therapy (ART) than in cells of healthy persons. The effect of MVA on cell surface receptors is mostly unknown. Using mass cytometry profiling, we investigated the expression of 17 cell surface receptors in leukocytes after ex vivo infection of human whole-blood samples with MVA. We found that MVA downregulates most of the characteristic cell surface markers in particular types of leukocytes. In contrast, C-X-C motif chemokine receptor 4 (CXCR4) was significantly upregulated in each leukocyte type of healthy persons. Additionally, we detected a relative higher cell surface expression of the HIV-1 co-receptors C-C motif chemokine receptor 5 (CCR5) and CXCR4 in leukocytes of HIV-ART patients than in healthy persons. Importantly, we showed that MVA infection significantly downregulated CCR5 in CD4+ T cells, CD8+ T cells, B cells, and three different DC populations. CD86, a costimulatory molecule for T cells, was significantly upregulated in HLA-DRbright DCs after MVA infection of whole blood from HIV-ART patients. However, MVA was unable to downregulate cell surface expression of CD11b and CD32 in monocytes and neutrophils of HIV-ART patients to the same extent as in monocytes and neutrophils of healthy persons. In summary, MVA modulates the expression of many different kinds of cell surface receptors in leukocytes, which can vary in cells originating from persons previously infected with other pathogens.